Determination of Maintenance Energy Requirements for Fattening Castrated Korean Black Goats (Capra hircus coreanae) - Sang-Ho Moon; Yeong Sik Yun; Na Yeon Kim; Sanguk Chung; Qi Man Zhang; Yujiao Tang; Sang-Hoon Lee; Jinwook Lee; Si Heung Sung; Mirae Oh (Animals, 2021)
Twelve adult (10 months old) castrated Korean black goats, with an average initial body weight of 24.98 ± 3.7 kg, were used in this experiment to determine their maintenance energy requirements. Dry matter intakes (g/d, p = 0.945) were not affected by energy levels, but metabolic energy intake (kcal/d, p < 0.002) and average daily gain (g/d, p < 0.001) were significantly increased at higher energy levels. Nutrient digestibility was similar in the treatments, but crude fat digestibility increased with the addition of protective fat powder (p = 0.001). The energy required for fattening the castrated Korean black goats was estimated using the correlation between metabolic energy intake per dietary body weight and average daily gain per dietary body weight. The Y-axis intercept value was calculated to be 108.76 kcal/kg BW0.75 (p < 0.05, r2 = 0.6036), which was the metabolic energy requirement for maintaining the lives of the fattening Korean black goats. The estimated energy requirements of the black goat can improve specification techniques, such as the energy level and the amount of feed supply required for domestic black goats.